Making Meaning: Utopian Method for Minds, Bodies, and Media in Architectural Design. Issue 1 (15th January 2018) - Waterman, Tim
Education is a practice of futurity. It seeks to prepare the minds and bodies that will construct and inhabit the future. Design in the architectural disciplines—the architectures—also prepares buildings (landscape, edifice, city, countryside) for future dwelling.1 This article examines the use of the imagination in the design process and how it may be employed to posit better future worlds despite, and counter to, the prevalence of neoliberal imaginaries. Utopianism as both pedagogical method and design process is presented, as is the employment of the senses to bring the site and its materials alive in the embodied imagination. Both are methods for envisioning scenarios for whole ecological, sensual, and emotional worlds to create better designs for dwelling spaces. Processes of making are shown as interwoven with imagined stories, simulations, and situations in a series of sections. Each section attempts to describe a whole realm of making. The sections are thus loosely held together within the structure of the article to allow the reader space for imagination and discovery in the terrae incognitae between them.